A week in the life of a Greco-Roman woman - Beers, Holly (A week in the life, 2019)
Day 1, Wednesday (Day of Mercury/Hermes) -- Day 2, Thursday (Day of Jupiter/Zeus) -- Day 3, Friday (Day of Venus/Aphrodite) -- Day 4, Saturday (Day of Saturnus/Kronos) -- Day 5, Sunday (Day of Sol/Helios) -- Day 6, Monday (Day of Luna/Selene) -- Day 7, Tuesday (Day of Mars/Ares).